2010
DOI: 10.1007/s10658-010-9607-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of aggressiveness and deoxynivalenol production between Canadian Fusarium graminearum isolates with 3-acetyl and 15-acetyldeoxynivalenol chemotypes in field-grown spring wheat

Abstract: Twenty four isolates of Fusarium graminearum, half of which were 3-acetyldeoxynivalenol (3-ADON) and half 15-acetyldeoxynivalenol (15-ADON) chemotypes, were tested for their ability to produce deoxynivalenol and to cause Fusarium head blight (FHB) in spring wheat cultivars. The objectives of this study were to determine (1) whether 3-ADON isolates differ in aggressiveness, as measured by the FHB index, and DON production from 15-ADON isolates under field conditions, and (2) whether the performance of resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 30 publications
4
47
1
Order By: Relevance
“…However, potential strain or population-specific differences in the total amount of trichothecene accumulated in grain is also of concern. In analyses of Canadian F. graminearum, 3-ADON strains accumulated significantly more DON in vivo than 15-ADON strains (von der Ohe et al 2010;Ward et al 2008). The prevalence of 3-ADON among Norwegian F. graminearum could therefore indicate a relatively larger threat to food safety in comparison to regions in which 15-ADON isolates predominate.…”
Section: Discussionmentioning
confidence: 96%
“…However, potential strain or population-specific differences in the total amount of trichothecene accumulated in grain is also of concern. In analyses of Canadian F. graminearum, 3-ADON strains accumulated significantly more DON in vivo than 15-ADON strains (von der Ohe et al 2010;Ward et al 2008). The prevalence of 3-ADON among Norwegian F. graminearum could therefore indicate a relatively larger threat to food safety in comparison to regions in which 15-ADON isolates predominate.…”
Section: Discussionmentioning
confidence: 96%
“…Gilbert et al (2010) reported that 15-ADON and 3-ADON chemotypes did not differ in their pathogenicity, but the 3-ADON chemotypes produced more DON, on average, than 15-ADON chemotypes. Von der Ohe et al (2010) also found that the 3-ADON chemotypes produced more DON than 15-ADON chemotypes, after inoculation, in wheat that was rated as moderately resistant. Puri and Zhong (2010) reported that 3-ADON chemotypes in the laboratory produced more DON and conidia compared with 15-ADON chemotypes.…”
Section: Mots Clé Smentioning
confidence: 95%
“…Fusarium graminearum produce DON, nivalenol (NIV) and zearalenone, as well as, 3-acetyl deoxynivalenol (3-ADON), 15-acetyl deoxynivalenol (15-ADON) (Ichinoe et al 1983;Miller et al 1991;O'Donnell et al 2000). However, some 15-ADON chemotypes produced both 15-ADON and 3-ADON in grain after inoculation (Von der Ohe et al 2010). Fusarium poae and F. sporotrichioides have been reported to be capable of forming HT-2, and T-2 (Foroud and Eudes 2009).…”
Section: Mots Clé Smentioning
confidence: 99%
“…chemotype in resistant and susceptible wheat cultivars. [12,48] The increase in the incidence of F. graminearum and F. culmorum populations in the eastern Mediterranean region of Turkey could potentially have resulted in increased levels of DON and reduced levels of NIV contamination in wheat grains, depending on the toxin profile of both Fusarium species. However, the high proportion of DON chemotype, found within the F. graminearum and F. culmorum populations, as reported here, indicated that DON contamination was high and NIV contamination was low in wheat grains in the eastern Mediterranean region of Turkey.…”
Section: Pcr Amplificationmentioning
confidence: 99%